2011
DOI: 10.1289/ehp.1003369
|View full text |Cite
|
Sign up to set email alerts
|

Black Carbon as an Additional Indicator of the Adverse Health Effects of Airborne Particles Compared with PM 10 and PM 2.5

Abstract: Background: Current air quality standards for particulate matter (PM) use the PM mass concentration [PM with aerodynamic diameters ≤ 10 μm (PM10) or ≤ 2.5 μm (PM2.5)] as a metric. It has been suggested that particles from combustion sources are more relevant to human health than are particles from other sources, but the impact of policies directed at reducing PM from combustion processes is usually relatively small when effects are estimated for a reduction in the total mass concentration.Objectives: We evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
576
2
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 954 publications
(602 citation statements)
references
References 77 publications
13
576
2
11
Order By: Relevance
“…The included studies used different methods, and their relation and conversion factors have been described previously [102]. All-cause mortality was significantly associated with elemental carbon, and the meta-analysis resulted in an RR of 1.061 per 1 μg/m 3 EC (95% CI 1.049–1.073).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies used different methods, and their relation and conversion factors have been described previously [102]. All-cause mortality was significantly associated with elemental carbon, and the meta-analysis resulted in an RR of 1.061 per 1 μg/m 3 EC (95% CI 1.049–1.073).…”
Section: Resultsmentioning
confidence: 99%
“…Black carbon affects the optical properties of the atmosphere when suspended and is recognized as the second most important anthropogenic forcing agent for climate change after CO 2 (Ramanathan and Carmichael, 2008;Bond et al, 2013). Black carbon is also the leading indicator of the adverse health effects caused by particulate air pollution (Janssen et al, 2011(Janssen et al, , 2012Grahame et al, 2014). Reducing air pollution is a major societal need, which must be addressed at a local, national, regional and global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Featuring high light-absorbing 20 efficiency, BC would exert substantial impact on climate change at regional and even global scale (Bond et al, 2013;Menon et al, 2002;Ramanathan and Carmichael, 2008). Meanwhile, BC has been proven to be inextricably linked to short-term changes in public health such as cardiovascular mortality and cardiopulmonary hospital admissions (Eklund et al, 2014;Janssen et al, 2011). A recent study by has revealed the vital role of BC in enhancing near-surface haze pollution by the combined effects of heating by the light-absorbing BC aerosols in upper-PBL and the reduction of surface 25 heat flux, which substantially suppresses the development of PBL and consequently causes extreme haze pollution episode in China's megacities.…”
Section: Introductionmentioning
confidence: 99%